Basket hasil tangkapan dan keterkaitannya dengan mutu hasil tangkapan dan sanitasi di TPI PPN Palabuhanratu - Anwar Bey Pane (Jurnal Ilmu Pertanian Indonesia, 2008)
Fish basket has an important role in assisting efficacy of marketing and fish landing process at fishing port. Generally have been known the function of basket as place of fish conveyor. Basket that was used during the time in fishing port (FP) and fish landing  place (FLP), indication of apperance of uncleanness at port quay, fish auction place (FAP/TPI) and it surrounding. The problem of sanitaion and also fish quality as ports at this period are very important for FP/FLP in Indonesia, especially for facing the era of globalization and free market. Including for FP such as PPN Palabuhanratu will be developed into ocean fishing port type; with one of function is to provide the fish for export purposes. This research was conducted at PPN Palabuhanratu at period of Sep-Nov 2007, the aims of this research are for knowing the effect of useful of basket to fish quality and the port quay sanitation, FAP and its surrounding. This research using study case method that is research the catch aspect in FP and fish basket aspect of catch landing and marketing activities and port quay and FAP. In PPN Palabuhanratu, the existing of fish basket are have so many type; plastic basket, bamboo basket, barrel, styrofoam box and container fibreglass (jolang). The use of its have affect to fish quality differently: assisting to maintain and degrade the quality of fish. Almost all type of fish basket have negative influence to sanitaion of port quay, FA and its surrounding, except box of styrofoam for layur. No one of the type of fish basket are able to provide only positive influence on fish quality and satation.